PARTISIPASI POLITIK PEREMPUAN DAN KEBIJAKAN PUBLIK DI PROVINSI BANTEN - Delly Maulana (Universitas Serang Raya, 2013)
The existence of affirmative policy rules applied in 2009 election has been successful to increase the number of women in parliament. Within the scope of Banten Province, the quota for women's political participation is still not fully utilized by Bantenese women, although there is a significant increase in the general election in 2004 with the election in 2009, and placing women in formal political space such as Governor, Mayor, and Vice Regent in the two districts. Furthermore, the implementation of the Regional Regulation About Gender mainstreaming (Bylaw No. 10 of 2005 and regulation No. 39 of 2006 on Guidelines for the Regional Action Plan for Gender Mainstreaming in Banten province) is not strong enough to provide a significant increase in the development of gender-based violence in Banten province, it is seen of IPG and IDG that are still below national standards. These conditions proved that increasing women's political participation in Banten still puts oligarchs at the local level (political family, a network of local elites and the ruling political party affiliation).